THE USE OF LEARNING MEDIA SNAKES AND LADDERS FOR IMPROVING STUDENTS' ACTIVENESS IN SMP NEGERI 12 BANJARMASIN - Rahmia, Sovia Husni; Amelia, Sri; Sari, Raihanah; Triyono, Sigit; Syarifuddin, Syarifuddin (International Conference On Social Science Education, 2024)
Snakes and Ladders media is a learning tool that combines traditional game concepts with educational material. The use of snakes and ladders learning media increases student involvement in social studies subjects at SMP Negeri 12 Banjarmasin. Snakes and Ladders is implemented as a learning medium which aims to increase active participation, raise enthusiasm, and create a pleasant learning experience for students. The research method used is a qualitative approach with case studies involving observation and interviews. The research results show that the use of snakes and ladders learning media significantly increases the level of student activity and learning outcomes, demonstrating an increase in enthusiasm for learning, improved communication skills, and problem-solving skills since the introduction of this learning medium. This article provides an in-depth understanding of how this media can enhance student interaction and involvement in the learning process, offering guidance for educators in utilizing innovative and effective learning media. This research highlights the effectiveness of the snakes and ladders learning media in increasing active participation, raising enthusiasm, and creating an enjoyable learning experience for students.